1998
DOI: 10.1111/j.1524-4725.1998.tb04145.x
|View full text |Cite
|
Sign up to set email alerts
|

Earlobe Reconstruction Using a Subcutaneous Island Pedicle Flap after Resection of “Earlobe Keloid”

Abstract: In the selected cases, use of the subcutaneous island pedicle flap is a viable method to be considered for reconstruction after resection of earlobe keloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…However, even though the size of the keloid may decrease with nonsurgical treatment alone for the cases of larger lesions, the results may not be cosmetically satisfactory. Various surgical methods such as excision followed by primary suture 14 , healing by secondary intention 15 , skin graft 16 or local flap 17 have been used. Yet surgical excision alone has shown varying degrees of success and perioperative nonsurgical therapies should be combined to prevent the inevitable recurrence after surgical excision.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though the size of the keloid may decrease with nonsurgical treatment alone for the cases of larger lesions, the results may not be cosmetically satisfactory. Various surgical methods such as excision followed by primary suture 14 , healing by secondary intention 15 , skin graft 16 or local flap 17 have been used. Yet surgical excision alone has shown varying degrees of success and perioperative nonsurgical therapies should be combined to prevent the inevitable recurrence after surgical excision.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with keloids often experience marked physical deformity, restricted range of motion, pain, pruritus and psychological problems . Different treatment modalities such as radiation, pressure therapy, cryotherapy, intralesional injections of steroids, interferon 5‐fluorouracil (5‐FU), topical silicone, http://PDL, excision followed by primary suture, healing by secondary intention,and skin flap and graft have been used for treatment of keloids. It has been suggested that fibroblasts derived from keloid and hypertrophic scar tissue produce increased amounts of collagen compared with normal fibroblasts, Thus, suppression of the overwhelming and uncontrolled fibroblast activity in keloids and hypertrophic scars may be essential in therapeutic approaches to these abnormal wound responses…”
mentioning
confidence: 99%
“…Primary suture an close the defect after excision of small keloids but keloids requiring surgical excision are usually large. [13][14][15][16][17] Simple suturing usually maintains tension in closure that promotes keloid recurrence and distorts the reconstructed earlobe. Shaving associated with cryosurgery seems to be a useful treatment for large keloids scars.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a "keloid fillet flap" enables dissection of the keloid core leaving loose skin to effect closure while an island flap uses skin bordering the defect. 5,6 Decreased recurrence rates have been reported with excision in combination with other postoperative modalities such as radiotherapy, injected interferon (IFN) or corticosteroid therapy. Excisional surgery alone has been shown to yield a 45-100% recurrence rate.…”
Section: Introductionmentioning
confidence: 99%